Enhancement of coffee brew aroma through control of the aroma staling pathway of 2-furfurylthiol. (30th August 2020) - Sun, Zhenchun; Cui, Heping; Yang, Ni; Ayed, Charfedinne; Zhang, Xiaoming; Fisk, Ian D.
Highlights: 2-Furfurylthiol (2-FFT) was not available for perception after storage of coffee. 2-FFT was lost due to interaction with oxidation products of hydroxyhydroquinone. Cysteine & ascorbic acid (CYS&AA) released 2-FFT and mitigated coffee aroma staling. Nutty, sulfurous and roasted aroma attributes were enhanced with CYS & AA. Abstract: During storage of coffee, the key aroma 2-furfurylthiol becomes less active, the mechanisms of this loss and ways to mitigate it were investigated. Aroma profiles were analyzed using GC–MS and sensory properties were evaluated by Quantitative Descriptive Analysis. Quinones, as the oxidation products of hydroxydroquinone, was found to actively bind 2-furfurylthiol, which accounted for the loss of 2-furfurylthiol. To mitigate this loss, ingredients were screened for their ability to prevent 2-furfurylthiol from loss. Cysteine had the highest 2-furfurylthiol releasing efficiency and ascorbic acid was also selected due to its 2-furfurylthiol releasing ability in Fenton reaction system. Concentrations were optimized and the addition of 0.045 g/L cysteine and 0.05 g/L ascorbic acid directly protected aroma during storage, these included 2-furfurylthiol, dimethyltrisulfide, methyl furfuryl disulfide, 4-ethylguaiacol and 4-vinylguaiacol. Ultimately, sensory testing showed a direct enhancement in nutty, sulfurous and roasted aroma attributes, an increase in flavour intensity and preference over shelf life.